Desmoceratidae and Silesitidae (ammonitida) from the Aptian - Albian of Antarctica - Medina, Francisco Alberto; Riccardi, Alberto Carlos (Neues Jahrbuch für Geologie und Paläontologie - Abhandlungen)
Aptian-Albian Desmoceratidae and Silesitidae of James Ross Island, Antarctica are described. Desmoceratid Puzosiinae are represented by Parasilesites IMLAY, Pseudosilesites EGOIAN, Feruglioceras LEANZA, Umsinenoceras KENNEDY et al., and Silesitidae by species of Neoastieria EGOIAN, Piatnitzkyceras MEDINA & RICCARDI, and Sobraliceras gen. nov. On James Ross Island several assemblage zones are recognized: the Peltocrioceras assemblage zone (Upper Aptian) is characterized by Pseudosilesites russoi (LEANZA); the Ptychoceras assemblage zone (Lower Albian) by Feruglioceras piatnitzkyi LEANZA, Umsinenoceras sp. indet., U.? sp. nov., Neoastieria antarcticaensis sp. nov., Piatnitzkyceras thomsoni sp. nov., Sobraliceras stoneleyi gen. et sp. nov. and 5.? sp. nov.; the Aioloceras assemblage zone (Lower Albian) is characterized by Piatnitzkyceras cf. bonarellii MEDINA & RICCARDI, Umsinenoceras cardielense MEDINA & RICCARDI, U. compressum sp. nov., Parasilesites jamesrossi sp. nov., P. densicostatus sp. nov., and Sobraliceras robustum gen. et sp. nov. Fil: Medina, Francisco Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina Fil: Riccardi, Alberto Carlos. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina